CW Doppler Radar as Occupancy Sensor: A Comparison of Different Detection Strategies - Gennarelli, Gianluca; Colonna, Vittorio Emanuele; Noviello, Carlo; Perna, Stefano; Soldovieri, Francesco; Catapano, Ilaria (Frontiers in Signal Processing, 2022)
Indoor occupancy sensing is a crucial problem in several application fields that have progressed from intrusion detection systems to automatic control of lighting, heating, air conditioning and many other presence-related loads. Continuous wave Doppler radar represents a simple technology to face this problem due to its capability to detect human body movements (e.g. walk, run) and small chest wall vibrations associated to the cardiorespiratory activity. This work deals with a radar prototype operating at 2.4 GHz as a real-time occupancy sensor. The emphasis is on data processing approaches devoted to extract useful information from raw radar signal. Three different strategies, designed to detect human presence in indoor environments, are considered and the main goal is the assessment and comparison of their performance against experimental data collected in controlled conditions. The first strategy is based on the analysis of the standard deviation of the radar signal in time-domain; whereas the second one exploits the histogram of the time-varying signal amplitude. Finally, a third strategy based on an energy measure of the received signal Doppler spectrum is considered. The proposed detection algorithms are optimized through a set of calibration measurements and their performance and robustness are assessed by laboratory trials.